2020
DOI: 10.1177/1099800420938141
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Kynurenine Pathway and Psychoneurological Symptoms Among Adult Cancer Survivors

Abstract: The co-occurrence of multiple psychoneurological symptoms, including pain, sleep disturbance, fatigue, depression, anxiety, and cognitive disturbance among adult cancer survivors led us to question which common biological mechanisms are shared among these conditions. Variances in tryptophan (Trp) levels and downstream metabolites of the kynurenine (Kyn) metabolic pathway are known to affect immune response and psychoneurological symptoms. The objective of this systematic review was to help us (a) better unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Our study found that metabolic pathways of fatty acids, bile acids, and amino acids were associated with the PNS in children with chemotherapy. These results were consistent with previous work from adult cancers (Li et al, 2020; Lyon et al, 2018). Specifically, moderate-to-strong correlations were found between changes in pain and tryptophan concentration and kynurenine/tryptophan ratio, as well as between changes in depression and serotonin level in women with breast cancer (Lyon et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…Our study found that metabolic pathways of fatty acids, bile acids, and amino acids were associated with the PNS in children with chemotherapy. These results were consistent with previous work from adult cancers (Li et al, 2020; Lyon et al, 2018). Specifically, moderate-to-strong correlations were found between changes in pain and tryptophan concentration and kynurenine/tryptophan ratio, as well as between changes in depression and serotonin level in women with breast cancer (Lyon et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…As symptoms often occur in clusters, they may also share a common biological aetiology 1,19,30,34 . For example, a psychoneurological symptom cluster (for example, involving pain, fatigue, anxiety, depression, pain, sleep disturbance and cognitive dysfunction) has been consistently observed among patients with cancer -a population that has a similar level of symptom experience to that of patients with advanced CKD [57][58][59][60] .…”
Section: Pathophysiology Of Ckd Symptomsmentioning
confidence: 99%
“…Alternatively, between-patient differences in the gut microbiome and putative modulatory effects of micronutrients may have a role 77,78 . As an example, alterations in the metabolism of tryptophan -an essential amino acid that is derived from dietary sources and contributes to the synthesis and regulation of neurotransmittersmight contribute to symptoms relating to sleep, mood and pain 58,79,80 , as well as the increased risk of cardiovascular disease 81 among patients with CKD. Tryptophan is the precursor of a number of signalling molecules, including the neurotransmitter serotonin, the hormone melatonin and vitamin B3 (niacin), all of which have important roles in the regulation of depression and sleep 79 .…”
Section: Pathophysiology Of Ckd Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the wide prevalence of anxiety and depression among breast cancer survivors, studies exploring the relationship between monoamine levels and such disorders in this population are scarce and inconclusive (Li et al, 2020). Pertl et al (2013) found no association between depression and KYN levels either during cancer treatment or six weeks after finishing chemotherapy or radiation therapy.…”
Section: Introductionmentioning
confidence: 99%